BIG STYLE IN SMALL SPACE : Easy DIY Projects to Add Designer Details to Your Apartment, Condo or Urban Home - Dorsey, Sarah (Salem, Massachusetts : Page Street Publishing Co., 2019)
This new decor book offers DIY enthusiasts simple yet impressive projects to give their homes the clean, modern and bright aesthetic that's popular in modern home design. Drawing on the same payoff that has made A Touch of Farmhouse Charm and French Vintage D cor popular, readers can give their homes designer style on a budget, without a lot of time or effort. Sarah Dorsey's minimalist, chic style is perfect for the large market of urban professionals living in small apartments or condos. Transform cheap stock pieces and raw materials into personalized, stylish furniture that makes a statement in any room. Readers' friends and family will be impressed with their home's impeccable style, even more so when they learn the pieces were handmade!
Includes index.
Keywords: Furniture finishing; House furnishings; Small rooms -- Decoration; Interior decoration; Handbooks and manuals